Analisis Sifat Mekanik Komposit Berbahan Serat Bulu Ayam - Acep Rahmat Hidayat; Widyantoro Widyantoro (edujavare, 2024)
The utilization of chicken feather waste as a reinforcement material for composites is an innovative approach to producing products from abundant natural materials in the surrounding environment. This study aims to evaluate the tensile and bending strength of composites reinforced with chicken feather fibers. The materials used in this research include chicken feather fibers, polyester resin, and mekpo catalyst. The sample fabrication technique involves pressing at room temperature. Tensile strength testing is conducted using a Zwick Roell tensile testing machine, while bending strength testing is performed using a Universal Testing Machine (UTM). The results indicate that chicken feather fiber-reinforced composites exhibit varying tensile strengths depending on the weight fraction (Wf) percentage of chicken feather fibers used. At a Wf of 0%, the tensile strength reaches 28 MPa, whereas at a Wf of 20%, the tensile strength decreases to 8.88 MPa. At a Wf of 28%, the tensile strength increases to 15.84 MPa but decreases again at a Wf of 35% to 8.27 MPa. Meanwhile, for bending strength tests, the chicken feather fiber-reinforced composites show varying results, with both Wf 0% and 20% achieving a bending strength of 24 MPa. However, at a Wf of 28%, the bending strength decreases to 18 MPa and further decreases to 12 MPa at a Wf of 35%.This study demonstrates that the utilization of chicken feather fibers as a composite reinforcement has significant potential, although its efficiency greatly depends on the concentration of fibers used. Further research is needed to optimize the composition and production methods to achieve composites with better mechanical properties and broader applications in the industry.